Plasticine modeling of material mixing in friction stir welding - Malik, Vinayak; Kailas, Satish V. (Journal of materials processing technology, 2018)
Plasticine of primary colours was utilized and the hue attribute of generated secondary colour was tracked. The degree of mixing was indicated by the intensity of secondary colour. Hue component was obtained from digital images of joined plasticine cross-section by converting RGB colour-maps to HSV colour-maps. Effect of tool pin profile that included circular, hexagonal, square and triangular was examined in this context. As the number of faces on the tool pin reduces, up-till pin with four faces (square) the pin induced mixing increases and results in the elimination of joint line remnant. Material adjacent to the face was transported in lumps and experienced spinning/whirling movement. During mixing phenomenon flow velocities of constituents undergoing it tends to fluctuate. The fluctuation is significantly large for higher levels of mixing and the same was noticed for a square profile from the results of finite element simulations. The results obtained from plasticine and finite element simulations are validated using aluminium weld.